Switched-Capacitor-Based Modular T-Type Inverter - Lee, Sze Sing; Lee, Kyo Beum (IEEE Transactions on Industrial Electronics, 2021)
Switched-capacitor-based multilevel inverters have been gaining increasing attention in recent years in view of their voltage-boosting capability and capacitor self-balancing properties. However, the existing topologies, which comprise frontend switched-capacitor cells and a backend H-bridge, result in longer discharging duration in some of their switched-capacitors. In addition, the adoption of backend H-bridge introduces common-mode voltage and necessitates multiple dc sources for voltage level extension. To resolve these problems, this article proposes a novel topology comprises a T-type inverter and n cascaded switched-capacitor cells. It requires only a single dc source and it manages to mitigate the common-mode voltage by connecting the neutral of ac output to the mid-point of dc link. All switched-capacitors in the proposed topology are ensured to be charged for at least half of the fundamental period to alleviate the capacitor voltage ripples and current spikes. The operation of the proposed topology is analyzed and experimental results are presented for validation.
Keywords: Capacitor voltage ripple; Common mode voltage; Fundamental period; Multilevel inverter; Single dc source; Switched capacitor; Switched capacitor cells; Voltage boosting; Multilevel inverter; switched capacitor; T-type inverter; voltage boosting